L’analyse des interactions didactiques dans la formation initiale des enseignants de français langue seconde - Violaine Bigot (Communiquer)
First studied in the field of discourse and interaction analysis, then in the field of second language acquisition research, second language classroom interaction has more recently been studied in the field of “occupational didactic”. In France, second language classroom interaction was slowly integrated as a legitimate object in the field of language teaching research but it still plays a marginal role in second language teacher’s training. This article analyzes this slow legitimation and the effective contribution of these researches in the academic French as a second language teacher’s training program. It also underlies some of the difficulties that emerge when basing a training course on second language analysis.